Pengelolaan Dana Desa untuk Peningkatan Pembangunan di Desa Toriyo Kecamatan Bendosari Kabupaten Sukoharjo - Dewandaru, Hafidz Anugerah; Madalina, Maria (Res Publica: Jurnal Hukum Kebijakan Publik, 2021)
ABSTRACTThis research aims to find out how was the management of Village Fund at Toriyo village in Bendosari sub-district of Sukoharjo District in supervision of the Village Fund Allocation in accordance with Law Number 6 of 2014 concerning Villages. Based on Government Regulation No 60 of 2014 juncto Government Regulation No. 8 of 2016 about Village Fund sourced from State Budget and Expenditure as well as analyze the obstacles that arise in the management of the Fund. The author of this research choose the empirical legal research with descriptive character using qualitative approach, research method that generates descriptive analytical data that is stated by the respondents according to their writing or orally also real behavior, that is researched and studied as a whole. This research uses the secondary and primary sources. While the sources collection technique carried out trough  interview and observation. Considering the result of research and discussion, it could be stated that the management of Village Fund at Toriyo village in Bendosari sub-district of Sukoharjo District were appropriate with the applicable law, but it still have obstacles that occurred because of the late report from the country side which got the stimulants fund of Village Fund at Toriyo village. The late report occurred because of the country side people still unfamiliar with the existence of Village Fund. So that, a socialization concerning on technical management of the Village Fund is needed. This socialization purpose is to adjust the implementation of the applicable Law concerning on Village Fund Management.Keywords : management; village fund; development.